H[underscore]/H[infinity] fault detection observer design for a polytopic LPV system using the relative degree - Zhou, Meng; Rodrigues, Mickael; Shen, Yi; Theilliol, Didier (Zielona Góra: Uniwersytet Zielonogórski)
This paper proposes an H[underscore]/H[infinity] fault detection observer method by using generalized output for a class of polytopic linear parameter-varying (LPV) systems. As the main contribution, with the aid of the relative degree of output, a new output vector is generated by gathering the original output and its time derivative, and it is feasible to consider H[underscore] actuator fault sensitivity in the entire frequency for the new system.
Keywords: H[underscore]/H[infinity] fault detection observer; polytopic LPV systems; relative degree of output; actuator fault detection; sensor fault detection